Low-energy N-ion beam biotechnology application in the induction of Thai jasmine rice mutant with improved seed storability - Nuananong Semsang (2018)
© 2018 Elsevier B.V. Low-energy heavy-ion beam is a novel biotechnology used for mutation induction in plants. We used a low-energy N-ion beam to induce mutations in Thai jasmine rice (Oryza sativa L. cv. KDML 105) to improve the yield and seed quality. Seeds of BKOS6, a Thai jasmine rice mutant previously induced by ion beams, were re-bombarded with 60-kV-accelerated N-ions (N + +N 2 + ) to fluences of 1–2 × 10 16 ions/cm 2 . The resulting mutant, named HyKOS21, exhibited photoperiod insensitivity, semi-dwarfness, and high yield potential. Seed storability of the mutant was studied in natural and accelerated ageing conditions and compared to that of KDML 105 and six other Thai rice varieties. In both testing conditions, HyKOS21 mutant had the highest seed storability among the tested varieties. After storage in the natural condition for 18 months, HyKOS21 had a seed germination percentage nearly two times as that of the original KDML 105. Biochemical analysis showed that the lipid peroxidation level of the mutant seeds was the lowest among those of the tested varieties. Furthermore, an expression analysis of genes encoding lipoxygenase isoenzyme (lox1, lox2, and lox3) revealed that the mutant lacked expression of lox1 and lox2 and expressed only lox3 in seeds. These results may explain the improved seed longevity of the mutant after storage. This work provides further evidence of the modification of biological materials using a low-energy ion beam to produce rice mutants with improved yield and seed storability. The benefits of this technology, to create new varieties with improved values, could serve for local economic development.